2021
DOI: 10.3390/ijerph18052375
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Bisphenol A and Phthalates with Risk of Breast Cancer: A Meta-Analysis

Abstract: Background: Breast cancer is the most common cancer and the second leading cause of cancer-related death amongst American women. Endocrine-disrupting chemicals (EDCs), especially bisphenol A (BPA) and phthalates, have adverse effects on human health. However, the association of BPA and phthalates with breast cancer remains conflicting. This study aims to investigate the association of BPA and phthalates with breast cancer. Methods: Correlative studies were identified by systematically searching three electroni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 63 publications
0
23
0
Order By: Relevance
“…Women were found to be exposed at higher levels than men due to frequent use of PCPs (e.g., soaps and cosmetics) [ 26 ]. A systematic review and meta-analysis concluded that phthalates metabolites MBzP and MiBP were negatively associated with breast cancer among females [ 27 ]. Risk assessment of chemicals involves a comparison of the actual level of exposure to the acceptable level of exposure, mostly TDI values.…”
Section: Phthalates Toxicology and Risk Assessmentmentioning
confidence: 99%
“…Women were found to be exposed at higher levels than men due to frequent use of PCPs (e.g., soaps and cosmetics) [ 26 ]. A systematic review and meta-analysis concluded that phthalates metabolites MBzP and MiBP were negatively associated with breast cancer among females [ 27 ]. Risk assessment of chemicals involves a comparison of the actual level of exposure to the acceptable level of exposure, mostly TDI values.…”
Section: Phthalates Toxicology and Risk Assessmentmentioning
confidence: 99%
“…For example, experimental evidence suggests that neonatal exposure to Di-2-ethylhexylphthalate (DEHP) leads to dysfunction of the male reproductive system (Lee et al, 2021). DEHP metabolites have also been associated with an increased odds for breast cancer in case-control studies (Liu et al, 2021), although a prospective study did not show associations between phthalate and breast cancer risk (Reeves et al, 2019). Cross-sectional epidemiological studies further indicate associations between higher urinary phthalates levels and obesity (Song et al, 2014), insulin resistance (Stahlhut et al, 2007), diabetes (Nam et al, 2020), and cardiovascular diseases (CVD) (Zhu et al, 2021).…”
Section: Tablementioning
confidence: 99%
“…The exposure to these ED has been linked to reproductive impairments and infertility, neurodevelopmental disorders, hormone-dependent cancers, obesity, diabetes, thyroid disorders, oxidative stress, genotoxicity, although the relationships with some of these health endpoints are still controversial (Bledzka at al. 2014;Dabre and Harvey, 2008;Hauser and Calafat, 2005;Heudorf et al, 2007;Katsikantami et al, 2016;Liu et al, 2021;Ma et al, 2019;Rochester, 2013;Soni et al, 2005). Because of the potential health risk related to our exposure to these chemicals, some restrictions and regulations have been progressively implemented worldwide since early 2000's.…”
Section: Introductionmentioning
confidence: 99%